Multi-Band Magnitude Complementary Crossover Network by Using Q-Bernstein Filter - Sookcharoenphol, Dolchai; Janchitrapongvej, Kanok (My University, 2024)
This paper presents a multi-band magnitude complementary (MC) crossover network by using Q-Bernstein filter (QBF). The prototype low-pass filter is used the Q-Bernstein polynomial (QBP) to approximate a desired function. The QBF gives parameters which can be changing stop-band attenuation of the filter. The magnitude responses show that the filter gives high attenuation values in the stop-band of degree 2. The two-band MC crossover network can be realized by cascading an all-pass filter and a constant voltage of degree 1, which sums up to the all-pass filter (APF) of degree 2. The multiple-bands crossover network can be realized by cascading two identical all-pass filter stages of degree 2. The simulation results show that the proposed crossover network has a constant summed magnitude response and also an in-phase response over an audio band.
Keywords: All-Pass Crossover Network; Flat pass-band; In-Phase Digital Crossover Network; Magnitude Complementary Q-Bernstein Filter Pair